Smart Home Automation - Kumar, Anoop; Goswami, Shubham; Goel, Swati (International Journal of Computer Sciences and Engineering, 2019)
The “Home Automation” concept is an approach to wirelessly control the home appliances. The terms “Smart Homes”, “Intelligent Homes” are associated with this kind of system and has been used to introduce the networking concepts based appliances and devices in the house. Smart homes and home control system ideas have grown along with the enhancement in technology and the constant improvement of the living standards of humans. Home automation Systems represents a great research opportunity in developing new ideas in the fields of engineering, architecture and computing. The people using home automation can access the use of appliances anytime and from anywhere, making our houses become more and more automated and intelligent. The Smart Energy initiative fulfils these abundant needs by providing an adoptable and sustainable experience by linking new and useful digital technologies to the requirements of consumers.